Ewolucja "Lamusa" - od lokalnego periodyku o charakterze literacko-artystycznym po quasi-naukowe czasopismo specjalistyczne o zasięgu ogólnopolskim = Evolution of "Lamus" - from a local literary and artistic periodical to a quasi-scientific, specialized nationwide magazine - Turska, Magdalena (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article concerns the literary and artistic magazine "Lamus" published in the years 1993-2014 in Gorzów Wielkopolski. It covers the periodical`s evolution over this period based on the magazine`s content. The aims of the article are to analyze the corpus and outline the background of local periodicals in order to highlight the role of "Lamus" in Gorzów Wielkopol-ski. At the time it was published, it was one of the most influential regio-nal literary magazines.
Keywords: "Lamus" - czasopismo; czasopiśmiennictwo; ewolucja; czasopismo literacko-artystyczne; twórczość artystyczna; region; magazines; evolution; literary and artistic magazine; artistic creativity